Implementing Person-Centred Lean Six Sigma to Transform Dermatology Waiting Lists: A Case Study from a Major Teaching Hospital in Dublin, Ireland - Aileen Igoe; Seán Paul Teeling; Orla McFeely; Michelle McGuirk; Siobhan Manning; Vanessa Kelly; Heather Coetzee; Úna Cunningham; Karen Connolly; Patsy Lenane (Sci)
The study site, a major teaching hospital in Dublin, Ireland, addressed significant challenges within its dermatology service through a comprehensive improvement initiative using a person-centred Lean Six Sigma methodology. Initially, the hospital’s dermatology department faced excessive outpatient waiting times, with 3736 patients awaiting appointments, and 1615 waiting over 12 months. The person-centred Lean Six Sigma approach, which combines Lean techniques to reduce non-value add and Six Sigma methods to eliminate variation through a person-centred lens, was applied to overhaul the referral, triage, and scheduling processes. Key interventions included standardising triage categories, centralising the triage process, and redistributing referrals equitably among consultants. A new centralised triage system was established, leading to a more efficient allocation of appointments and better management of urgent cases. Post-implementation data showed a 40% reduction in the overall waiting list and a 60% reduction in the number of patients waiting over 12 months. The initiative significantly decreased the wait times across all urgency categories, with the most notable improvements in soon and urgent referrals. These changes were also the impetus for a follow-up design-led innovation phase, where the team worked with partners across the educational and healthcare system to enable disruptive change. The success of this project provides a scalable model for improvements in similar healthcare settings.